Cortisol, Platelet Serotonin Content, and Platelet Activity in Patients With Major Depression and Type 2 Diabetes: An Exploratory Investigation. Issue 2 (February 2015) - Zahn, Daniela; Petrak, Frank; Franke, Leonora; Hägele, Anna-Karolina; Juckel, Georg; Lederbogen, Florian; Neubauer, Horst; Norra, Christine; Uhl, Idun; Herpertz, Stephan
ABSTRACT: Objective: Hypothalamic-pituitary-adrenal system dysfunction, serotonergic system alterations, and enhanced platelet activity may contribute to the increased cardiac risk in depression. This exploratory study examined associations between cortisol parameters, platelet serotonin (5-HT) content, and platelet activity markers in patients with newly diagnosed major depression (MD) and/or Type 2 diabetes (T2DM) compared with healthy controls. Methods: We compared cortisol awakening response (CAR), diurnal decrease in salivary cortisol concentrations (slope), platelet 5-HT, and platelet markers (CD40, CD40 ligand [CD40L], soluble CD40L, CD62P, β-thromboglobulin, and platelet factor-4) in 22 T2DM patients, 20 MD patients, 18 T2DM patients with MD, and 24 healthy controls. Results: Platelet markers were elevated in MD ( F (6, 60) = 11.14, p < .001) and T2DM ( F (6, 60) = 13.07, p < .001). Subgroups did not differ in 5-HT or cortisol slope, whereas T2DM patients without depression had significantly lower CAR than did healthy controls ( F (1, 61) = 7.46, p = .008). In healthy controls, cortisol slope correlated with platelet activity for CD40 ( r = −0.43, p = .048) and 5-HT was correlated with CD40L ( r = 0.53, p = .007). In patients with both T2DM and MD, 5-HT and CD62P were correlated ( r = 0.52, p = .033). Conclusions: Increased platelet activity in T2DM and MD may play a role in the association between diabetes, depression, and coronary artery disease. The present data suggest that group differences in cortisol or 5-HT as well as group-specific associations of cortisol or 5-HT with platelet markers might be of limited importance in the shared pathways of T2DM and depression in the pathophysiology of coronary artery disease.